Factors associated with positive outcome of avulsion injuries in children - Marković, Dejan; Vuković, Ana; Vuković, Rade; Soldatović, Ivan (Vojnosanitetski pregled, 2014)
Introduction/Aim. Avulsions are severe dental injuries with high impact on patients’ quality of life due to prolonged treatment and possible severe complications. The aim of the study was to analyze the epidemiological factors related to the occurrence, treatment and outcome of avulsions in Serbian children. Methods. This research included 2,194 patients aged 1–18 years with traumatic dental injuries. The history, demographic, clinical and radiographic data of the patients were observed from dental medical records. Results. A total of 266 avulsions were observed in 207 patients. The frequency of avulsions was 12% in primary dentition and 5% in permanent dentition. A statistically significant relationship between place, cause of avulsion and outcome was observed. Replantation of permanent teeth was performed in 46.7% with a mean time 6.9 h. Almost a half of permanently avulsed teeth (48.7%) were not retrieved from the accident site and 11.3% of replanted teeth were transported in adequate media. The observed incidence of complications was 31.9%. Conclusions. Replantation was not performed in more than a half of all eligible teeth due to either loss or inadequate/delayed transport, which emphasizes the need for preventive strategies and health education in population.